THERMAL PROCESSING ANALYSIS OF GRAPHENE OXIDE - Khanmamedova, E. (Collection of scientific papers «ΛΌГOΣ», 2023)
Graphene oxide thermal treatment means that graphene sheets are obtained by oxidation process and then subjected to thermal treatment by exposing them to high temperatures. This process changes the properties of the graphene oxide material, creating a coating that is resistant to high temperatures.